2004
DOI: 10.1261/rna.7138805
|View full text |Cite
|
Sign up to set email alerts
|

A pre-tRNA carrying intron features typical of Archaea is spliced in yeast

Abstract: Archaeal pre-tRNAs are characterized by the presence of the bulge-helix-bulge (BHB) structure in the intron stem-and-loop region. A chimeric pre-tRNA was constructed bearing an intron of the archaeal type and the mature domain of the Saccharomyces cerevisiae suppressor SUP4 tRNA Tyr . This pre-tRNA ArchEuka is correctly cleaved in several cell-free extracts and by purified splicing endonucleases. It is also cleaved and ligated in S. cerevisiae cells, providing efficient suppression of nonsense mutations in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In either case, it is the tRNA-splicing endonuclease that recognizes the splice sites (11). Previous work from Tocchini-Valentini and colleagues (12,13) has demonstrated that mature domain-independent splicing can occur in yeast or Xenopus if a sequence that will form a BHB structure is inserted into a model pre-tRNA or mRNA. Moreover, an exogenous archaeal endonuclease expressed endogenously in mammalian cells can splice a BHB structure inserted into a reporter mRNA (14).…”
mentioning
confidence: 99%
“…In either case, it is the tRNA-splicing endonuclease that recognizes the splice sites (11). Previous work from Tocchini-Valentini and colleagues (12,13) has demonstrated that mature domain-independent splicing can occur in yeast or Xenopus if a sequence that will form a BHB structure is inserted into a model pre-tRNA or mRNA. Moreover, an exogenous archaeal endonuclease expressed endogenously in mammalian cells can splice a BHB structure inserted into a reporter mRNA (14).…”
mentioning
confidence: 99%
“…1A, hybrid precursor 1; Thompson et al 1989). The BHB structure is typical of archaeal tRNA introns, and we have already demonstrated in vitro and in vivo that it is recognized and efficiently spliced by the eukaryal tRNAsplicing endonuclease (Fabbri et al 1998;Fruscoloni et al 2001;Di Segni et al 2005). It is conceivable that the BHB structure facilitates the folding of the tRNA body.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an artificial CCA sequence was added at the tRNA 3Ј-end. A mature tRNA can be obtained from this precursor if the tRNA splicing endonuclease cleaves at the pretRNA splicing sites, the cut ends are ligated, and a cleavage by RNase P occurs, leaving a mature 5Ј-end and a 3Ј-terminal CCA in the tRNA (20,22). Very recently, a similar gene organization has been found in a red alga (23).…”
Section: A Pretrna Sequence Can Be Removed From the Middle Of A Premrnamentioning
confidence: 97%
“…In a previous study, we have shown that long noncanonical pretRNA molecules, containing the BHB structure, are correctly cleaved and ligated in S. cerevisiae, producing functional tRNAs (20). Here, we addressed the question whether the yeast tRNA splicing system can specifically splice mRNA sequences.…”
mentioning
confidence: 99%